Stakeholder Perceptions of Adolescents' needs for Healthy Identity Formation in the Digital Era: A Qualitative Study - Keksi Girindra Swasti; Budi Anna Keliat; Yossie Susanti EKa Putri; Widyatuti Widyatuti (Jurnal Keperawatan Soedirman, 2026)
The presence of digital technology has brought changes to various aspects of human life, influencing the formation of individual character, particularly among adolescents whose primary developmental task is identity formation. This research employed an exploratory qualitative design to explore perceptions of digital technology and the needs of adolescents in identity formation amid the challenges posed by digital technology. Data were collected through focus group discussions and in-depth interviews with 24 participants selected using purposive sampling techniques. The focus groups included adolescents, parents, teachers, and nurses. In-depth interviews were conducted with the Elementary and Secondary Education Curriculum Section of the Banyumas Regency Education Office and the school health program coordinator at the Banyumas Regency Health Office. Data analysis was carried out using the Colaizzi approach. The study found that digital technology offers adolescents with opportunities to socialize, access knowledge sources, develop talents, creativity, and innovation, and boost self-confidence. However, excessive use of digital technology poses risks that threaten physical, emotional, and social well-being, potentially hindering identity formation. Adolescents require to have a strong character, self-regulation skills, and support from various parties working synergistically. These results providevaluable insights for designing appropriate interventions to support adolescent identity formation